Does the Iranian oil supply matter for the oil prices? - Mohammad Reza Farzanegan (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
There is an increasing tension between the Iranian Government and the west on an increasingly likely European oil embargo and the Iranian threat to close the Strait of Hormuz. The main question is: What will happen to the international oil prices in the case of shocks in the flow of Iranian oil to the international markets? In this study, we analyze the dynamic relationship between the Iranian oil supply and international oil prices from January 1973 - September 2011, using a modified version of the Granger causality test introduced by Toda and Yamamoto (1995). Our results show that there is no Granger causality between the Iranian oil production and international oil prices. Historical data on the Iranian oil production do not provide any useful information to explain the current and future values of international oil prices. Thus, global oil prices do not follow shocks in the Iranian oil production.
Keywords: E37; Q32; Q34; Q38; Q43; 330; Oil price; Oil production; VAR model; Granger causality; Sanction; Iran; Ölpreis; Mineralölpreisschock; Kausalanalyse; Schätzung; Welt; Erdölförderung; Mineralölwirtschaft; Iran